2017
DOI: 10.1007/s00277-017-2945-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase deficiency and risk of diabetes: a systematic review and meta-analysis

Abstract: Emerging epidemiological evidence suggests that patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency may have a higher risk of developing diabetes. The aim of the review was to synthesise the evidence on the association between G6PD deficiency and diabetes. A systematic search on Medline, EMBASE, AMED and CENTRAL databases for studies published between January 1966 and September 2016 that assessed the association between G6PD deficiency and diabetes was conducted. This was supplemented by a review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…117 MECP2 binds to methylated DNA and mediates transcriptional repression through interaction with histone deacetylase and the corepressor SIN3A (15q24.2 [MIM: 607776]) ( Figure S14). Lai et al 118 reported meta-results that T2D-affected case subjects with G6PD deficiency had two times higher odds of developing diabetes than unaffected control subjects. 119 Furthermore, G6PD protein has a weak score of 1 out of 5 to be found in MT.…”
Section: Mtdna and Metabolic Disease Associationsmentioning
confidence: 99%
“…117 MECP2 binds to methylated DNA and mediates transcriptional repression through interaction with histone deacetylase and the corepressor SIN3A (15q24.2 [MIM: 607776]) ( Figure S14). Lai et al 118 reported meta-results that T2D-affected case subjects with G6PD deficiency had two times higher odds of developing diabetes than unaffected control subjects. 119 Furthermore, G6PD protein has a weak score of 1 out of 5 to be found in MT.…”
Section: Mtdna and Metabolic Disease Associationsmentioning
confidence: 99%
“…Activity of alternative pathways provides robustness of NADPH supply and to some extent compensates deficit of PPP flux in patients with glucose-6 phosphate dehydrogenase (G6PD) deficiency, the most common genetic disease in humans [18]. Patients with G6PD deficiency generally have no symptoms and their lifespan is not affected by disease, but it was shown that in addition to increased hemolysis they are less resistant to some poisonings [18] and have higher risk of diabetes and metabolic syndrome [19]. Glucose-6 phosphate (G6P) is an exclusive substrate for G6PD, a rate limiting enzyme of PPP and in human organism can be supplied from extracellular space in the form of glucose, then phosphorylated by hexokinase.…”
Section: Basic Overview Of Glucose Metabolism and Its Role In Maintenmentioning
confidence: 99%
“…G6PD deficiency is the most common genetic human disease [18]. Since G6PD is a gateway to such an important metabolic pathway as PPP, dramatic consequences to the patients could be expected.…”
Section: Glucose-6 Phosphate Dehydrogenase Deficiencymentioning
confidence: 99%
“…It is likely that the other structural and functional interactions may exist in the cells in order to couple synergistic metabolic processes in response to oxidative stress. Activity of alternative pathways provides robustness of NADPH supply and to some extent compensates deficit of PPP flux in patients with glucose-6 phosphate dehydrogenase (G6PD) deficiency, the most common genetic disease in humans [18]. Patients with G6PD deficiency generally have no symptoms and their lifespan is not affected by disease, but it was shown that in addition to increased hemolysis they are less resistant to some poisonings [18] and have higher risk of diabetes and metabolic syndrome [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation